ROLES OF MONITORING AND EVALUATION, TEACHING PARTICIPATION, AND GOVERNMENT ON TEACHING PRODUCTIVITY RESULT AND INSTITUTIONAL DEVELOPMENT PLANNING - Sahid, Ahmad Qurtubi (Journal of Islamic Education, 2020)
Lecturers as university educators have been main player and determinant of successful educational effort. Their roles are getting challenged when their role and productivity are highlighted. They face challenges which come from three sources, e.g., university standards; (2) education measurement; (3) issue of balancing government standards with institutional plan. However, there is a gap that lecturer’s efforts are rarely observed especially in college and universities. The purpose of this study is to determine whether programs that have been run by college have achieved the expected goals. This type of research is field research to observe college preparation and evaluation to measure their lecturers role in teaching and classroom interaction. Our study found that M E and lecturers active role can impact on the teaching productivity. We also found that lecturers understanding about government policy can improve college ability to develop their institutional plan. This study bring benefits for management auditors, institutional planner and educators to develop and improve their institutional plans.Keywords: monev, the active role of the lecturers, the lecturers 's interactive role in the class discussion, the productivity of the lecturers